Empowerment of housewife in efforts of preventing covid 19 to children in Kelurahan Sunggal - Lutfhiani; Siregar, Cholina Trisa; Tanjung, Dudut; Ahmad, Ikhsanuddin; Ariga, Reni Asmara (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
COVID-19 is a type of virus that attacks the respiratory system that can affect anyone from infants to children to adults, including pregnant women and nursing mothers. This disease can spread rapidly through droplets that come out when the patient sneezes or coughs. Symptoms of this disease are often considered normal by the community, so that it has a risk of transmission and can spread to other people, especially children. Limited knowledge and ability in prevention needs to be improved by providing counseling and training to housewives. Actions taken by implementing efforts to maintain family health through increasing knowledge and knowing prevention measures for transmission to children. Minimizing the spread of disease requires continuous action, this requires the role of housewives as executors of health care for family members. Increasing the knowledge and skills of housewives is needed to help people overcome their health problems. Health problems in the community often occur, among others, due to inadequate knowledge of disease prevention, crowded environment, inadequate socio-economic conditions. Implementing actions by increasing public knowledge and training on ways to minimize the spread of infection is the concern and assistance of health workers.